Development of Visual Aspect of Porsche Brand using CAD Technology. (2015) - Aqeel, Anas Bin
Abstract: Brand identity is an important factor as it creates a connection between the product and the company. Consistent brand statement through its identification and differentiation is an important aspect towards the development of a successful product by which people can relate to the brand. However, due to inadequate understanding of brand by engineering, design and marketing, brand statement is difficult to preserve. This paper presents the novel CAD implementation technique to explore the visual aspects of Porsche car brand using shape grammar. A set of rule library is developed after a detailed investigation into the history of Porsche styling to highlight two – dimensional front view key elements of Porsche vehicles. This Porsche grammar supports in development of futuristic Porsche designs within its brand hierarchy.